2020
DOI: 10.3389/fmed.2020.625442
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Composite Angioimmunoblastic T-Cell Lymphoma and Epstein-Barr Virus-Positive B-Cell Lymphoproliferative Disorder as Other Iatrogenic Immunodeficiency-Associated Lymphoproliferative Disorders

Abstract: Immunosuppressants are widely used to treat patients with rheumatoid arthritis (RA), and their adverse effects have been known to cause other iatrogenic immunodeficiency-associated lymphoproliferative disorders (OIIA-LPDs). We report a patient with RA who had been treated with methotrexate (MTX) and tacrolimus (TAC) and who developed whole body lymphadenopathy. We simultaneously confirmed angioimmunoblastic T-cell lymphoma (AITL) through a right cervical lymph node biopsy and Epstein-Barr virus-positive B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Alternatively, the first appearance of T-cell lymphoma may also result in a deficiency in innate immunity that renders host B cells more susceptible to EBV infection, leading to transformation into B-cell neoplasms. In such cases, the patient’s T-cell and B-cell tumor components tend to be EBER positive ( 8 , 21 ). Although this patient was positive for EBV-associated IgG, the pathology indicated that EBER was negative for both T and B cell components.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the first appearance of T-cell lymphoma may also result in a deficiency in innate immunity that renders host B cells more susceptible to EBV infection, leading to transformation into B-cell neoplasms. In such cases, the patient’s T-cell and B-cell tumor components tend to be EBER positive ( 8 , 21 ). Although this patient was positive for EBV-associated IgG, the pathology indicated that EBER was negative for both T and B cell components.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, immunosuppressants, including methotrexate (MTX) and tacrolimus (TAC), are widely used to treat patients with rheumatoid arthritis (RA), and their adverse effects have been known to cause other iatrogenic immunodeficiency-associated lymphoproliferative disorders (OIIA-LPDs). Seiji reported that the tumor cells were positive for EBV in 8 (17%) of 48 patients; background cells were positive in 32 (82%) of 39 patients with available data in the literature review of MTX-associated T-LPDs (MTX T-LPDs) ( 68 ). The presence of EBV reflects a profound immunodeficiency and may drive the development or a rapid progression of the tumor.…”
Section: Discussionmentioning
confidence: 99%